Validation of SeaWiFS data from around New Zealand - Richardson, K.M.; Pinkerton, M.H.; Boyd, P.W.; Gall, M.P.; Zeldis, J.; Oliver, M.D.; Murphy, R.J. (Advances in space research, 2004)
The near-surface concentration of chlorophyll- a ( C a ) was measured during 11 research voyages around New Zealand between 1998 and 2000. Over 400 measurements of spectral normalised water-leaving radiance were made using a high precision profiling spectroradiometer. The data were used to assess the quality of remotely sensed measurements of C a by the NASA ocean colour sensor, SeaWiFS, in New Zealand waters. The results in the open-ocean regions are consistent with a combination of negative biases in the C a algorithm of ca. 20% (some regional dependency), and positive biases due to under-estimation of water reflectance towards the blue end of the spectrum by SeaWiFS.